Effect of poly(ε-caprolactone) modification on its biodegradation in natural environments - Rutkowska, M.; Krasowska, K.; Heimowska, A.; Steinka, I. (Polimery, 2022)
Effect of various modifiers and processing additives on poly(epsilon-caprolactone) (PCL) biodegradation rate under natural conditions (in compost with activated sludge and in seawater) was investigated. Tests included starch, chalk or processing additives (i.e. poly(ethyl-butyl acrylate) with oxidant (EBA), or Master Batch (MB) system consisting of PE-LD and crucic and oleic acid amides) modified PCL. Characteristic parameters of both environments were controlled throughout the biodegradation (Tables I and 2). Biodegradation of PCL was assessed based on changes in weight, intrinsic viscosity, tensile strength, surface morphology and crystallinity characteristics (Tables 3-6, Fig. 1). Susceptibility of PCL to biological degradation caused by macro- and micro-organisms present in the natural environment was confirmed. Biodegradation of unmodified PCL lasts 6 weeks in compost and 7 weeks in seawater. Chalk does not affect PCL biodegradability rate, whereas introduction of starch accelerates the process. Modification of PCL using processing additives reduced its susceptibility to attack by microorganisms present in the natural environment, thus, prolonging the biodegradation. Microscopic observations and DSC measurements confirmed two-stage enzymatic degradation of PCL, whereby the amorphous phase is degraded first, with the polymer crystalline phase following.